2008
DOI: 10.1159/000151344
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Determination of Serum Placental Protein 13 during Development of Preeclampsia

Abstract: Objective: To determine maternal serum placental protein 13 (PP13) in normal pregnancy and preeclampsia. Methods: A prospective, longitudinal study with 41 normal pregnant women, 18 cases with preterm delivery or cervix insufficiency and 4 with developing late-onset preeclampsia. Six hundred and sixty-six maternal blood samples were obtained every 2–4 weeks starting at 5–8 weeks gestation (10–12 samples/patient) and tested for serum PP13 by ELISA. Results: In normal pregnant women delivering at term, median ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
2
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 44 publications
4
124
2
9
Order By: Relevance
“…13 Compared with O group, A, B, and AB groups are associated with an increased risk of thrombotic events, although this relationship is debated. ABO blood groups may differ in the occurrence of known vascular risk factors for preeclampsia, such as endothelial dysfunction 14 , insulin resistance, 15 and hypercholesterolemia. 16 ABO blood group is a key determinant of coagulation factor VIII and von Willebrand factor plasma concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…13 Compared with O group, A, B, and AB groups are associated with an increased risk of thrombotic events, although this relationship is debated. ABO blood groups may differ in the occurrence of known vascular risk factors for preeclampsia, such as endothelial dysfunction 14 , insulin resistance, 15 and hypercholesterolemia. 16 ABO blood group is a key determinant of coagulation factor VIII and von Willebrand factor plasma concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of SNPs in the LGALS13 gene and of shorter PP13 isoforms, which are not recognized by the current PP13 ELISA test, might explain the lower values of PP13 in the first trimester of pregnant women who subsequently develop preeclampsia [6].…”
Section: Mutations In the Lgals13 Gene And Their Impact On The Use Ofmentioning
confidence: 93%
“…Renate Hillermann reported the identification of single nucleotide polymorphisms (SNPs) in the LGALS13 gene, which encodes placental protein 13 (PP13), a galectin expressed predominantly by the placenta [5][6]. Recent studies have demonstrated that patients who subsequently developed preeclampsia had lower maternal serum PP13 concentrations in the first trimester than women who had a normal pregnancy outcome [2,6].…”
Section: Mutations In the Lgals13 Gene And Their Impact On The Use Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Allerdings gelang die auf dem Verhältnis zwischen anti-und proangiogenetischen Faktoren basierende Vorhersage erst einige Wochen vor dem Auftreten von klinischen Symptomen. Die Aufmerksamkeit hat sich deshalb vermehrt auf die Suche nach Biomarkern im Zusammenhang mit Störungen bei der Implantation gerichtet, um durch eine frühe-re Vorhersage die Zeitspanne für eine effektive medikamentöse Prophylaxe zu erweitern [15,16].…”
Section: » Bei Der Präeklampsie Bleibt Die Umwandlung Der Spiralarterunclassified